Climate change in the Western Cape : a disaster risk assessment of the impact on human health - Louw, E. J. M. (Stellenbosch : University of Stellenbosch, 2008)
Thesis (DPhil (Geography and Environmental Studies))—University of Stellenbosch, 2007.